Prenatal health education using expository method as a prevention of stunting - Yunitasari, E; Maesaroh, S; Fauziningtyas, R; Emawati, A (International Journal of Psychosocial Rehabilitation, 2020)
As a global Issue since 2017, stunting is seen as a serious problem that should be solved immediately to reduce the prevalence of stunting. The incidence of stunting in Indonesia continues to increase, it is due to socio-ethnic conditions food belief especially in pregnant women in some regions. The aim of this study is to explain the influence of health education on pregnant women in preventing stunting. A quasy experiment with pre-post test design was conducted on 60 pregnant women in Bangkalan. A systematic simple random sampling technique was used to choose pregnant women with pregnancy <7 months and regularly perform antenatal care. Structured questionnaire was used to collect the data and analyzed using Wilcoxon and Mann Whitney test with a significance level of α <0.05. The result showed that there were the effectiveness of expository method using media booklets and card game on increasing knowledge (p=0,000), attitudes (p=0,000) and ability (p=0,000) in the treatment group. There were significant differences between the treatment and control group on knowledge (p=0,001), attitude (p=0,000), and ability (p=0,000) after the intervention. Prenatal education using expository methods effectively improves the knowledge, attitudes and ability of pregnant women as an effort to prevent stunting.